Ergosterol biosynthesis in Aspergillus fumigatus: its relevance as an antifungal target and role in antifungal drug resistance - Alcazar-Fuoli, Laura; Mellado, Emilia (Frontiers in Microbiology, 2013)
Ergosterol, the major sterol of fungal membranes, is essential for developmental growth and the main target of antifungals that are currently used to treat fatal fungal infections. Emergence of resistance to existing antifungals is a current problem and several secondary resistance mechanisms have been described in Aspergillus fumigatus clinical isolates. A full understanding of ergosterol biosynthetic control therefore appears to be essential for improvement of antifungal efficacy and to prevent antifungal resistance. An ergosterol biosynthesis pathway in A. fumigatus has been proposed with fourteen sterol intermediates resulting in ergosterol and another secondary final compound C-24 Ethyl sterol. Transcriptomic analysis of the A. fumigatus response to host-imposed stresses or antifungal agents is expanding our understanding of both sterol biosynthesis and the modes of action of antifungal drugs. Ultimately, the identification of new targets for novel drug design, or the study of combinatorial effects of targeting sterol biosynthesis together with other metabolic pathways, is warranted.